Karakteristik minuman fermentasi bubuk dengan kultur starter Lactobacillus achidopillus dengan penambahan tepung umbi porang - Hasna Rahma Aulia; Lulu Eki Daysita; Molina Indah Pradiva; Dewi Nandyawati; Amanda Dwi Gebrina; Fatim Illaningtyas; Wike Zahra Mustafawi (AGROINTEK, 2024)
Porang tuber is a local Indonesian commodity whose utilization is still low for becoming food or beverage products. Porang tuber contains high glucomannan, so probiotic bacteria can utilize it. Therefore, it has the potential to be a prebiotic agent. This study aims to determine the characteristics of fermented beverages with Lactobacillus acidophilus culture with variations in the concentration of porang tuber flour application. The study utilized a Completely Randomized Design (CRD) with a single treatment factor, specially the concentration of added porang tuber flour. Physicochemical analysis was carried out using SPSS Version 16.0 with significance level 5%. Based on statistical test, the addition of porang tuber flour significantly influenced the viscosity and pH of the fermented beverage. The best treatment was the fermented drink formula with the addition of porang tuber flour by 0.4%, which had a pH of 4.85 ± 0.03, viscosity of 20 ± 2.18 mpas, and cell viability of lactic acid bacteria before drying at 8.71 log cfu/ml and after drying at 6.64 log cfu/ml, respectively. The reformulation of dry powder fermented beverage with adding 0,4% porang tuber flour at 50% was the most preferred in the organoleptic test.